PENGARUH EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION MELALUI CUSTOMER SATISFACTION SEBAGAI INTERVENING VARIABEL (Studi Pada The Bagong Adventure Museum Tubuh) - Andrianto, Dwi Gusti (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research is aimed at determining and analyzing the effect of experiential marketing on repurchase intention through customer satisfaction as intervening variable (study at The Bagong Adventure Museum Tubuh). This is an explanatory research. The sampling technique used is non probability sample with purposive sampling method. The sample in this study comprised 110 respondents who are the visitors of The Bagong Adventure Museum Tubuh. Data used in this study are primary data and secondary. Data collection instrument is questionnaire measured by using Likert scale. This study uses Partial Least Squares (PLS), supported by software SmartPLS 3.0, and sobel test is used to examine the relations of the mediating variables. The results showed that experiential marketing consisting of sense, feel, think, act, and relate is able to simultaneously increase repurchase intention of The Bagong Adventure Museum Tubuh. Experiential marketing consisting of sense, feel, think, act, and relate is able to simultaneously increase customer satisfaction of The Bagong Adventure Museum Tubuh. Customer satisfaction is able to increase repurchase intention of The Bagong Adventure Museum Tubuh. Experiential marketing consisting of sense, feel, think, act, and relate through customer satisfaction has a positive impact on repurchase intention of The Bagong Adventure Museum Tubuh.KEYWORDS: Experiential Marketing, Customer satisfaction, Repurchase Intention